In-situ construction of Co(OH)2 nanoparticles decorated urchin-like WO3 for highly efficient degradation of sulfachloropyridazine via peroxymonosulfate activation: Intermediates and DFT calculation - Xi Tao; Poyueh Pan; Taobo Huang; Long Chen; Ji, Haodong; Juanjuan Qi; Fengbin Sun; Liu, Wen (Chemical Engineering Journal, 2020)
Sulfachloropyridazine (SCP) was commonly used as a broad-spectrum sulfonamide antibiotic and hard to be removed through traditional sewage treatment process. In this study, we developed a simple and controllable strategy to realize in-situ construction of Co(OH)2 nanoparticles decorated urchin-like WO3 (Co(OH)2/WO3), which could efficiently remove SCP through peroxymonosulfate (PMS) activation. Some tiny nanoparticles of Co(OH)2 decorated on the spines/nanorods or surfaces of urchin-like WO3 by transmission electron microscopy (TEM) analysis. The obtained 10 wt% Co(OH)2/WO3 realized completely removal of SCP (degradation efficiency 100%) with a high reaction rate constant (k1) of 0.88 min−1 within 3 min at optimal pH 7. That was because the urchin-like WO3 with numerous adsorption functional groups on its surface (e.g., W = O and –OH bonds) could adsorb the Co2+ easily to form CoOH+, which was perceived the rate-limiting step for PMS activation and generating radicals. Radical quenching experiments indicated that SO4•− played a more significant role than HO• radicals. Density functional theory (DFT) calculation revealed that the atoms of SCP with high Fukui index (f−) were active sites, which preferred to be attacked by the electrophilic SO4•− and HO• radicals. The toxicity of the intermediates by SCP degradation was evaluated by quantitative structure–activity relationship (QSAR) prediction through Toxicity Estimation Software Tool (T.E.S.T.). The possible degradation pathway and catalytic mechanism for SCP removal were proposed. Considering the good catalytic properties of Co(OH)2/WO3-PMS, the material will show great application potential in the removal of emerging contaminants in water.
Keywords: Co(OH)/WO; DFT calculation; Intermediates; Peroxymonosulfate (PMS); Sulfachloropyridazine